(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The development of technology creates a new phenomenon in human life, one of which is virtual objects (virtual property). This study aims to find and examine various concepts about virtual objects and the position of virtual objects in the Civil Code. This research is normative legal research, using a conceptual approach and a statutory approach. The data used are primary, secondary and tertiary. The data is analyzed qualitatively. The results show that: (1) The term virtual object is not known in the Civil Code but rather intangible objects because the Civil Code has existed and been in force since May 1, 1948, while the virtual world only developed in 1970. (2) Virtual objects are categorized as objects because they meet the elements: can be mastered/attached rights by humans, can be captured by the five senses or not, can be valued with money, or economic value, is a unity of owner and object. Because virtual objects are known and exist in the virtual world, one element is added that is formed through the interconnection of computer networks. (3) The position of virtual objects in the Civil Code shall be limited insofar as intangible or disembodied objects are concerned. This is a consequence of a constantly changing society, with rules in that society. Law developed as an alternative that could follow society’s development according to its era’s needs. (4) Along with legal developments that follow the development of society related to virtual objects, although limited, it has been regulated in several regulations outside the Civil Code, namely Law Number 28 of 2014 concerning Copyright and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions.